A comparison of analytical methods to assess the stability of self-oscillations in relay circuits and systems - A. G. Deripaska; M. V. Soklakova; E. P. Chernishev (Известия высших учебных заведений России: Радиоэлектроника)
A comparative evaluation of the results of analytical calculation of the self-oscillations and stability analysis techniques is provided developed for symmetric self-oscillations with repetitions through halfperiod and asymmetric with repetitions through the period.